Promoting psychological crisis coping through physical activity: The mediating roles of rumination and emotion regulation among college students - Yang Yang; Bochun Lu; Shimeng Wang (PLoS ONE, 2026)
This study examined the associations between physical activity and crisis coping among college students, with a particular focus on the potential mediating roles of rumination and emotion regulation strategies, including expressive suppression and cognitive reappraisal. A total of 1,033 Chinese college students (615 males, 418 females; aged 17–23 years, M = 20.30, SD = 1.59) completed self-report questionnaires. Structural equation modeling was used to test the proposed mediation and chain mediation models. The results indicated that physical activity was associated with both adaptive and maladaptive dimensions of crisis coping. In addition, significant indirect associations were observed through rumination, expressive suppression, and cognitive reappraisal. Two chain-mediated pathways involving rumination and emotion regulation strategies were also supported. Together, these findings suggest that rumination and emotion regulation are relevant psychological processes linking physical activity with crisis coping. This study contributes to a more nuanced understanding of how physical activity relates to crisis coping by highlighting the roles of cognitive and emotional regulation processes. The findings may inform the development of physical activity–based approaches that consider both cognitive and emotional factors in supporting college students’ mental health.